Influence of Person-Organization Fit, Compensation, and Work-Life Balance on Employee Performance - Ridhovan, Andreanov; Hadi Nugroho , Sukmo (Research Horizon, 2025)
Person-Organization Fit has become a key factor in fostering harmony and employee engagement with the organization's culture and values. Well-managed Compensation and Work-Life Balance play a crucial role in enhancing employee performance. The aim of this research is to explore the influence of Person-Organization Fit, Compensation, and Work-Life Balance on Employee Performance with the mediation of Job Satisfaction and Organizational Commitment. This study was designed using purposive sampling method involving 375 employees from several banks in Jabodetabek that have implemented Person-Organization Fit. Data was processed using SmartPLS 3.0 tools. The findings of this study indicate that Person-Organization Fit, Compensation, and Work-Life Balance have a significant influence on employee Job Satisfaction. Additionally, this research also demonstrates that Job Satisfaction has a significant influence on Organizational Commitment. However, there is no significant influence between Person-Organization Fit and Compensation on Organizational Commitment. The managerial implications of this research for management emphasize the importance of human resource management in considering the alignment between individuals and organizations, fairness in compensation, as well as support for the balance between employees' work and personal lives in creating a positive and productive work environment.